Comparative study on moisture absorption of kenaf bast and core fibre reinforced unsaturated polyester composites - Abdullah, Abdul Hakim; Ishak, Mohamad Ridzwan; Abdan, Khalina; Leman, Zulkiflle; Salit, Mohd Sapuan (2009)
One of the major drawbacks for natural fibre composites to deal with outside applications is the moisture absorption. This paper describes evaluation of the water absorption capacity of different core fibre and bast fibre on kenaf fibre reinforced unsaturated polyester composite. Bone dry test specimens 5%, 10%, 20%, 30% and 40% of fibre volume fraction were immersed in water for 48 hours. Neat unsaturated polyester specimens were used as a control. Series of SEM analysis were done and shows evidence of composite structures. The core fibres have larger moisture content capacity rather than bast fibres on diameter basis. Finally, it shows that moisture uptake increase with fibre volume fraction increases due to increased voids and eventually cellulose content.